Danza Abend: un grupo independiente fundado por la maestra Cristina Gigirey - Dorries-Gigirey, Gabriela (2020)
The beginnings and evolution of Danza Abend are inseparable from the artistic practice and teaching of the teacher Cristina Gigirey. It is impossible to refer to Abend without mentioning Gigirey, from her origins in her motherland Uruguay, and how she came to Costa Rica, where her artistic career, practice and teaching are legacies that remain over time. The following is an itinerary of this artistic group that gathers the major milestones of experimental and performing Costa Rican dance which had, as well, Latin American projection.